A new strategy for the chemoenzymatic synthesis of glycopeptides by De-O-acetylation with an esterase and glycosylations with glycosyltransferases. (June 2020) - Yoshimura, Yayoi; Nagashima, Izuru; Yokoe, Takayuki; Kishimoto, Toshimitsu; Shimizu, Hiroki; Chiba, Yasunori
Abstract: Glycopeptides are fragments of glycoproteins and are important in evaluating the biological roles of carbohydrates in glycoproteins. Fmoc solid-phase peptide synthesis using acetyl-protected glycosylated amino acids is a common strategy for the preparation of glycopeptides, but this approach normally requires chemical de- O -acetylation with a base that β-eliminates sugar residues and epimerizes the peptide backbone. Here we demonstrate a facile new chemoenzymatic synthetic strategy for glycopeptides, using an esterase for the de- O -acetylation of sugar residues and glycosyltransferases for successive sugar elongations at neutral pH. Graphical abstract: Image 1 Highlights: Deacetylation of glycopeptide with an esterase prevents base-induced side reactions, b-elimination and epimerization. An esterase from B. subtilis was utilized for deacetylation of sugar hydroxyl groups on glycopeptide synthesis. Deacetylation with an esterase and glycosylations with glycosyltransferases were accomplished in one-pot.